Myeloid‐derived growth factor (MYDGF) protects bone mass through inhibiting osteoclastogenesis and promoting osteoblast differentiation. (24th January 2022) - Xu, Xiaoli; Li, Yixiang; Shi, Lingfeng; He, Kaiyue; Sun, Ying; Ding, Yan; Meng, Biying; Zhang, Jiajia; Xiang, Lin; Dong, Jing; Liu, Min; Zhang, Junxia; et al.
Abstract: Whether bone marrow regulates bone metabolism through endocrine and paracrine mechanism remains largely unknown. Here, we found that (i) myeloid cell‐specific myeloid‐derived growth factor (MYDGF) deficiency decreased bone mass and bone strength in young and aged mice; (ii) myeloid cell‐specific MYDGF restoration prevented decreases in bone mass and bone strength in MYDGF knockout mice; moreover, myeloid cell‐derived MYDGF improved the progress of bone defects healing, prevented ovariectomy (OVX)‐induced bone loss and age‐related osteoporosis; (iii) MYDGF inhibited osteoclastogenesis and promoted osteoblast differentiation in vivo and in vitro ; and (iv) PKCβ‐NF‐κB and MAPK1/3‐STAT3 pathways were involved in the regulation of MYDGF on bone metabolism. Thus, we concluded that myeloid cell‐derived MYDGF is a positive regulator of bone homeostasis by inhibiting bone resorption and promoting bone formation. MYDGF may become a potential novel therapeutic drug for osteoporosis, and bone marrow may become a potential therapeutic target for bone metabolic disorders. SYNOPSIS: Myeloid‐derived growth factor (MYDGF) positively regulates bone homeostasis by inhibiting bone resorption and promoting bone formation. Myeloid cell specific MYDGF deficiency decreases bone mass and bone strength in mice. MYDGF restoration prevents decreases in bone mass and bone strength in mice. MYDGF inhibits osteoclastogenesis and promoted osteoblast differentiation in vivo and in vitro . PKCβ‐NF‐κB and MAPK1/3‐STAT3 pathways are involved in the regulation of MYDGF on bone metabolism. Abstract : Myeloid‐derived growth factor (MYDGF) positively regulates bone homeostasis by inhibiting bone resorption and promoting bone formation.